SMS's at the Public Broadcaster to control editorial decision-making - Plaatjies, Lydia-Anne (My University, 2012)
This study looks at how short message services (SMS’s) was used at the Public Broadcaster to control decision making during the period November 2008 and April 2009. The main argument of this thesis is: 1. How did mobile phones reconfigured control in the newsroom of the public broadcaster 2. The public broadcaster management and the SABC newsroom in Johannesburg did not fulfil the mandate of the public broadcaster doing the study period because of political pressure via SMS 3. Editors did not protect journalists and producers against those with political power. The reason for doing this study is that there are many studies that focus on the positives of digital technologies but very little research has been done about the possible negatives of this innovation in the newsroom. The study acknowledges the advantages of having digital technology as an added communication tool in the newsroom but argues that people with political power can also use mobile technology as surveillance tool to control the decision-making process in the newsroom. SMS’s as a digital technology contributed to a new form of control in the newsroom and sending and receiving of SMS made it difficult for news editors to follow proper news decision-making processes and editorial guidelines which impacted on the role of the public broadcaster. This resulted in either self-censorship, job insecurity or some people even left the newsroom. The literature review gives an overview of the principles of public broadcasting, such as autonomous, inclusive and balanced with very little interference and how it is realised within the structure and dynamics of the newsroom. The study looks at theories of control, and gatekeeping, gatewatching as an editorial function and the impact of SMS’s on these established roles in the newsroom. The study provides a theoretical understanding of political control and its interplay with and effects on the public broadcaster mandate. The research methodology is grounded in the qualitative paradigm. The methods utilised is a case study and semi-structured interviews supported by archived newspaper articles to answer the question: how short message services (SMS’s) was used at the Public Broadcaster to control decision making.
M.A. University of the Witwatersrand, Faculty of Humanities (Journalism and Media Studies), 2012